Environmental & Architectural Phenomenology Vol. 33, No. 1 - Kansas State University. Architecture Department (Environmental Architectural Phenomenology, 2021)
Besides “Items of interest,” and “citations received,” this issue includes the following items: Philosopher Quill R. Kukla’s City Living (Oxford Univ. Press, 2021); Phenomenologists Michael and Max van Manen’s Classical Writings for a Phenomenology of Practice (Routledge, 2021); Philosopher Sebastian Luft’s Subjectivity and Lifeworld in Transcendental Phenomenology (Northwestern Univ. Press, 2021, softcover); Philosopher Jeff Malpas’ Rethinking Dwelling (Bloomsbury, 2021); Architects Akkelies van Nes and Claudia Yamu’s Introduction to Space Syntax in Urban Studies (Springer, 2021, open-access). The issue also includes two essays: zoologist Stephen Wood’s consideration of becoming familiar with a natural place; and religious-studies scholar Harry Oldmeadow’s portrait of the holiness of mountains.